Developing Nutrition Awereness Students Using The Five Levels Of Prevention Concept In The Kuala Lumpur - Burhanddin, Nurfardiansyah; Yusriani, Yusriani; Agustini, Tutik (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2025)
Adolescence is a crucial period requiring special attention to nutritional fulfillment, as the nutritional needs during this age are the highest compared to other age groups. Observations at Sanggar Bimbingan Muhammadiyah Kampung Baru Kuala Lumpur revealed several nutritional issues among students, such as unbalanced eating habits, unhealthy snack consumption, Body Mass Index (BMI) below 18.5, and low knowledge of balanced nutrition. To address these issues, a student nutrition awareness program was proposed, utilizing the five levels of prevention concept.The program employed a participatory approach through brainstorming, demonstrations, group discussions, and hands-on training. Activities included training, coaching, and monitoring students' nutritional status, with evaluation conducted using pre- and post-test questionnaires and skill checklists. The program also aligns with the Key Performance Indicators (KPI) of Higher Education Institutions, namely KPI 2 (students gaining off-campus experience), KPI 3 (faculty engaging in off-campus activities), and KPI 5 (faculty outputs utilized by society). The program outcomes demonstrated significant improvements in students' knowledge, attitudes, and practices in implementing the concept of nutrition awareness based on the five levels of prevention. The outputs included enhanced student competencies in disseminating information and practicing balanced nutrition, the development of a Pocket Book on Healthy Eating Patterns and Balanced Nutrition, publication in the ABDIMASNU journal, media coverage in Rakyat Sulsel and Legion News, and the preparation of a comprehensive program report. This initiative is expected to contribute to raising nutritional awareness among adolescents in the community.